"FROM THE INDUS TO CONSTANTINOPLE": THE NAPOLEONIC WARS AND THE EVOLUTION OF A "MIDDLE EAST", 1798–1809. Issue 4 (7th August 2020) - Mens, Jay
Abstract : This article argues that Napoleon Bonaparte's attempt to reach India, firstly through Egypt and then through Qajar Persia, inaugurated the 'Middle East' as a coherent political space in international politics. The ostensibly existential threat posed by French schemes to British dominion over India prompted British Indian officials to perceive Egypt, Persia and the Gulf Emirates through the lens of Indian defence and European geopolitics for the first time. By the end of this period, these lands were imagined as a salient, somewhat coherent political space between "the Indus and Constantinople". This first 'Middle East' was the product of the globalization of European geopolitics and the need to defend British India, auguring the future of the region, in which its political importance, and even its location, was constructed in relation to the broader context of international affairs.